PENGARUH PUPUK MULTIFUNGSI TERHADAP PERTUMBUHAN RUMPUT ODOT (Pennisetum Purpureum CV. MOTT) - Siswoyo, Purwo; Rusdhi, Alfath; Kurniawan, Media Agus; Putra, Andhika; Pradana, Tengku Gilang; Negara, Adhona Bhajana Wijaya (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The purpose of this study was to determine the effect of multifunctional fertilizers on the growth of odot grass (Pennisetum purpureum cv. Mott). This research will be conducted in Sampecita Village, Kutalimbaru District, Deli Serdang Regency. This study used a completely randomized design with 5 treatments and 4 replications. The treatment in this study consisted of P0 = entisol soil without multifunctional fertilizer, P1 = 1 L multifunctional fertilizer without water, P2 = 1 L multifunctional fertilizer with 2 L of water solvent, P4 = 1 L multifunctional fertilizer with 4 L of water solvent, and P6 = 1 L multifunctional fertilizer with 6 L of water solvent. Data collection was carried out in this study, namely: observation by direct observation of the growth of odot grass with the use of Multi Function Fertilizer. Parameters observed were: plant height, leaf length, leaf width were measured using a meter and dry matter production. Fertilization using a multifunctional fertilizer on the production of odot grass has shown that fertilizing odot grass using a 1 L multifunctional fertilizer with 4 L of water solvent (P4) is the best result for the production of fresh and dry matter compared to other treatments or controls.